The Origins of Apparent Ijtihad by Ibn Hazm and Examples of Sub-Applications - Nas, محمد أمين (Dirasat: Shari'a and Law Sciences, 2022)
Objectives: The study aims to clarify the concept of ẓāhirī ijtihad by addressing some of the aspects that are inevitable, such as the term ẓāhir, ijtihad, and then ẓāhirī ijtihad with a primary focus on the origins, milestones, and paths of this ijtihad, and some of the sub-issues that Ibn Hazm al-Zahiri reached according to his ẓāhirī ijtihad. Methods: Scientific methods suitable for this purpose, such as the descriptive, inductive, and analytical methods were applied. Results: The research found that the origins of ẓāhirī ijtihad are the Qur’an and the Sunnah, with the prominent meanings required by the words contained in them, in their absolute pronunciation, or in their necessary sense. Another origin is the consensus (ijmāʿ) of the Companions before they dispersed, and that is about thawkheef. An additional origin is evidence, with its multiple types. The last is Istishab. Conclustions: The research recommendeds that care should be taken when conducting research aimed at revealing fundamentalist paths, prominent meanings, and concepts that are still obscured in our rich jurisprudential heritage of Muslim mental and intellectual maturity.